Put the answer choice numbers where the x’s are in the equation and then solve. The ones that are equal to 0 once solved will be your answer
Answer:
![(\sqrt{2},-1),(-\sqrt{2},-1)](https://tex.z-dn.net/?f=%28%5Csqrt%7B2%7D%2C-1%29%2C%28-%5Csqrt%7B2%7D%2C-1%29)
(StartRoot 2 EndRoot, negative 1) and (negative StartRoot 2 EndRoot, negative 1)
Step-by-step explanation:
we have
----> equation A
-----> equation B
solve by substitution
substitute equation B in equation A
![-2x^{2} +(-3x^{2} +5)=-5](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20%2B%28-3x%5E%7B2%7D%20%2B5%29%3D-5)
solve for x
![-5x^{2} +5=-5](https://tex.z-dn.net/?f=-5x%5E%7B2%7D%20%2B5%3D-5)
![-5x^{2}=-10](https://tex.z-dn.net/?f=-5x%5E%7B2%7D%3D-10)
![x^{2}=2](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D2)
![x=\pm\sqrt{2}](https://tex.z-dn.net/?f=x%3D%5Cpm%5Csqrt%7B2%7D)
<em>Find the value of y</em>
For
---->
For
---->
therefore
The solutions are
![(\sqrt{2},-1),(-\sqrt{2},-1)](https://tex.z-dn.net/?f=%28%5Csqrt%7B2%7D%2C-1%29%2C%28-%5Csqrt%7B2%7D%2C-1%29)
(StartRoot 2 EndRoot, negative 1) and (negative StartRoot 2 EndRoot, negative 1)
So you start by dividing 6 out of the expression and you get 6(4-3)
Answer: C O R R E C T
Step-by-step explanation: